Ruscogenin Ameliorates Experimental Nonalcoholic Steatohepatitis via Suppressing Lipogenesis and Inflammatory Pathway. (20th July 2014) - Lu, Hung-Jen; Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Chia Ju; Yang, Cheng; Wu, Ming-Chang; Liu, I-Min
Abstract : The aim of the study was to investigate the protective effects of ruscogenin, a major steroid sapogenin in Ophiopogon japonicus, on experimental models of nonalcoholic steatohepatitis. HepG2 cells were exposed to 300 μ mol/l palmitic acid (PA) for 24 h with the preincubation of ruscogenin for another 24 h. Ruscogenin (10.0 μ mol/l) had inhibitory effects on PA-induced triglyceride accumulation and inflammatory markers in HepG2 cells. Male golden hamsters were randomly divided into five groups fed a normal diet, a high-fat diet (HFD), or a HFD supplemented with ruscogenin (0.3, 1.0, or 3.0 mg/kg/day) by gavage once daily for 8 weeks. Ruscogenin alleviated dyslipidemia, liver steatosis, and necroinflammation and reversed plasma markers of metabolic syndrome in HFD-fed hamsters. Hepatic mRNA levels involved in fatty acid oxidation were increased in ruscogenin-treated HFD-fed hamsters. Conversely, ruscogenin decreased expression of genes involved in hepatic lipogenesis. Gene expression of inflammatory cytokines, chemoattractive mediator, nuclear transcription factor-(NF-) κ B, and α -smooth muscle actin were increased in the HFD group, which were attenuated by ruscogenin. Ruscogenin may attenuate HFD-induced steatohepatitis through downregulation of NF- κ B-mediated inflammatory responses, reducing hepatic lipogenic gene expression, and upregulating proteins in β -oxidation pathway.